Chinese Embroidery in Cultural and Creative Product Design (Journal of Fiber Bioengineering and Informatics, 2024)
Chinese embroidery is an important traditional craft that holds cultural significance and reflects theessence of Chinese culture. With the rise of the cultural creative industry, there is a growing demand forinnovative approaches to incorporating Chinese embroidery into a wide range of products. However, aresearch gap exists regarding methods to address this integration’s unique challenges and opportunitiesadequately. Therefore, this study explores the integration of Chinese embroidery into cultural andcreative product design through the synergistic utilisation of the Analytical Hierarchy Process (AHP),Quality Function Deployment (QFD) and the Theory of Inventive Problem Solving (TRIZ). This approachpresents a holistic and streamlined design methodology. AHP and QFD are employed to addresscustomer requirements, whereas TRIZ is employed to overcome technical obstacles and foster innovativesolutions. This study aims to bridge the research gap by combining qualitative and quantitativemethods to explore solutions for integrating Chinese embroidery into cultural and creative productdesign, tapping into its diverse artistic and cultural potentials. The research objective is to inspirethe development of more innovative and culturally significant products, integrating the elements andaesthetics of Chinese embroidery into cultural and creative product design. The significance of thisstudy lies in its incorporation of systematic methods and methodological innovation. Designers cancreate products that preserve and promote the rich heritage of Chinese embroidery within the realmof cultural and creative product design, ensuring its sustainability and evolution within the culturalcreative industry.
Keywords: Embroidery; Cultural and Creative Design; Product Design; AHP-QFD-TRIZ.